2021
DOI: 10.1002/lrh2.10269
|View full text |Cite
|
Sign up to set email alerts
|

Patients' roles in governance of learning: Results from a qualitative study of 16 learning healthcare systems

Abstract: Patient and family engagement has been identified as key to fulfilling Learning Healthcare Systems' (LHSs') promise as a model for improving clinical care, catalyzing research, and controlling costs. Little is known, however, about the state of patient engagement in the learning mission of these systems or about what governance structures and processes facilitate such engagement. Here, we report on an interview study of 99 patient and employee leaders in 16 systems. We found both variable levels of engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 22 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…A study of 16 LHSs in the United States found that the level of involvement may change over time and research is needed on how to consistently involve patients in LHSs. 63 Principles from several types of research could advance the concepts of LHSs in the stroke community. In addition to the opportunity for leveraging communitybased participatory research to increase patient, family, and stakeholder engagement in health care transformation, experts in community-based participatory research can also facilitate the more equitable involvement, collaboration, and integration of knowledge and ideas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 16 LHSs in the United States found that the level of involvement may change over time and research is needed on how to consistently involve patients in LHSs. 63 Principles from several types of research could advance the concepts of LHSs in the stroke community. In addition to the opportunity for leveraging communitybased participatory research to increase patient, family, and stakeholder engagement in health care transformation, experts in community-based participatory research can also facilitate the more equitable involvement, collaboration, and integration of knowledge and ideas.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 16 LHSs in the United States found that the level of involvement may change over time and research is needed on how to consistently involve patients in LHSs. 63…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,6 Patients are recognized as an important source of such knowledge. 7,8 Although LHSs routinely extract insights from patient data, the pace of translating these insights into innovations is slow and effectiveness inadequate. [8][9][10] As a result, many health care delivery organizations fall short of their potential as LHSs capable of evolving and innovating using knowledge obtained directly from their patients.…”
mentioning
confidence: 99%
“…16,17 Research has not yet fully assessed the potential value of patients' creative ideas or how to elicit them effectively across diverse populations for health system learning. 7,18 This study's objective is to fill that gap by examining new approaches to effectively obtain patients' creative ideas and how they may be utilized for quality improvement. Its first aim is to develop and test an entirely new method for systematically eliciting patients' creative ideas that combines strengths from existing approaches, namely patients' creative idea generation from codesign and utilization of representative knowledge from large-scale patient surveys.…”
mentioning
confidence: 99%
See 1 more Smart Citation